DEVELOPMENT OF DERIVATIVE TRADING ON FINANCIAL MARKET AND AGRIBUSINESS SECTOR IN SERBIA - Kuzman, Boris; Ercegovac, Dajana; Momčilović, Mirela (Economics of Agriculture, 2018)
Transactions with futures and other derivatives began their development in the XIX century on the exchanges in USA and other developed countries, but fnancial market in Serbia is still underdeveloped with exchange materials, volumes and number of participants. Investors on the Belgrade Stock Exchange mostly trade with stocks and government bonds. Also, Agrar Product Novi Sad has organized only spot trading of agricultural products. The paper goal is to present all relevant assumptions and signifcance of derivative trading development in Serbia with discussion about choice to start derivative trading on the already existing exchanges or to establish a new futures exchange that is going to be specialized for derivative trading. As the research method authors use content analysis and comparison of signifcant national and foreign literature with analyses of trading volumes on international and domestic exchanges. Authors recommend that Agrar Product Novi Sad be the frst in expansion of market listing with commodity futures and options. On this way market is going to be deeper, creating effcient mechanisms for investors protection from price risks, creating conditions for safer and long term production planning, with increase in market attractivity that could set the Agrar Product Novi Sad as a leader in commodity derivative trading in the South-East Europe.